Diagnostic value of oral "beefy red" patch combined with fingertip blood mean corpuscular volume in vitamin B12 deficiency - Xiaoheng Xu; Yang Liu; Xiaoqin Xiong; Yanmei Yao; Huiting Hu; Xiao Jiang; Wenxia Meng (BMC, 2022)
Abstract Objectives To investigate the diagnostic value of accessible fingertip mean corpuscular volume (MCV) combined with a visible "beefy red" patch in the diagnosis of vitamin B12 (VB12) deficiency in local clinics and hospitals without in-house clinical laboratories, especially in remote areas. Materials and methods The medical history data of patients complaining of oral mucosal pain at the Stomatological Hospital of Southern Medical University were reviewed. All included patients underwent fingertip blood routine examination, specific serological test (serum VB12, folic acid, iron, and ferritin), and detailed oral clinical examinations. According to the results of the serum VB12 test patients were divided into case and control groups. In diagnostic test, the diagnostic value of the "beefy red" patch and elevated MCV in VB12 deficiency was evaluated by the receiver operator characteristic curve. Results There were more female patients than male patients in the case group (serum VB12 level < 148 pmol/L, n = 81) and control group (serum VB12 level ≥ 148 pmol/L, n = 60), mostly middle-aged and elderly patients. There were no statistical differences in gender and age between the two groups. In the case group, the number of individuals with stomach disease was 13, the number of individuals with "beefy red" patch was 78, the number of individuals with oral ulcer was 29, the number of individuals with "MCV > 100fL" and "folic acid < 15.9 nmol/L" were respectively 68 and 5. All were more than that in control group (P < 0.05). The diagnostic test, "beefy red patch" has high sensitivity (0.963) but low specificity(0.883), "MCV > 100 fL" has high specificity (0.933) but low specificity (0.815), and "MCV > 100 fL combined with beefy red patch" has maximal specificity (0.950), and area under the curve (0.949). Conclusions Visible oral "beefy red" patch combined with accessible fingertip blood MCV could improve the rate of diagnosis in VB12 deficiency, especially in the elderly in local clinics and hospitals without in-house clinical laboratories in China, which is conducive to early disease detection and treatment.